2003
DOI: 10.1002/bit.10628
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the anaerobic process: Effects of volatile fatty acids

Abstract: A complex and fast dynamic response of the anaerobic biogas system was observed when the system was subjected to pulses of volatile fatty acids (VFAs). It was shown that a pulse of specific VFAs into a well-functioning continuous stirred tank reactor (CSTR) system operating on cow manure affected both CH(4) yield, pH, and gas production and that a unique reaction pattern was seen for the higher VFAs as a result of these pulses. In this study, two thermophilic laboratory reactors were equipped with a novel VFA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
3
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(79 citation statements)
references
References 35 publications
1
73
3
2
Order By: Relevance
“…This is in contrast to the ndings of Pind et al (2003) who observed an increase in CH 4 concentration as well as in pH after injecting VFAs. The reason for the converse reactions may be attributed to the neutralization with NaOH of the VFAs by Pind et al (2003).…”
Section: Resultscontrasting
confidence: 99%
“…This is in contrast to the ndings of Pind et al (2003) who observed an increase in CH 4 concentration as well as in pH after injecting VFAs. The reason for the converse reactions may be attributed to the neutralization with NaOH of the VFAs by Pind et al (2003).…”
Section: Resultscontrasting
confidence: 99%
“…Cow manure Temperature: thermophilic conditions Addition of VFA affected CH 4 yield, pH, and gas production Pind et al (2003) be a consequence of industrial activities that eliminate residues in the soil and aqueous media that in long term promote their accumulation (Glick 2003) with a majority of the sources being anthropogenic (Zhang et al 2005). For Cd, Pb, Cu and Zn, their toxicity increases as follows: Pb \ Zn \ Cu \ Cd (Bååth 1989), depending on numerous abiotic and biotic factors.…”
Section: Effects Of Heavy Metals On Anaerobic Processesmentioning
confidence: 99%
“…VFA started building up in the wastewater as the digestion proceeded and the maximum concentration of 2650 mg/ L was recorded at an OLR of 24.7 kg COD/m 3 .day. VFA has been recognized as one of the important intermediates during the anaerobic digestion (Wang et al, 1999;Ahring Angelidaki 1997) and is considered a central parameter for anaerobic treatment (Ahring and Angelidaki, 1995;Pind et al, 1999;2002). The impact of VFA accumulation was reflected in the marked decrease of COD removal from 86 to 68% when the OLR was increased to 24.7 kg COD/m 3 .day.…”
Section: T S Vsmentioning
confidence: 99%